Genotype/Phenotype Relationship in a Consanguineal Family With Brugada Syndrome Harboring the R1632C Missense Variant in the SCN5A Gene - Monasky, Michelle M.; Micaglio, Emanuele; Ciconte, Giuseppe; Benedetti, Sara; Di Resta, Chiara; Vicedomini, Gabriele; Borrelli, Valeria; Ghiroldi, Andrea; Piccoli, Marco; Anastasia, Luigi; Santinelli, Vincenzo; Ferrari, Maurizio; et al. (Frontiers in Physiology, 2019)
Brugada syndrome (BrS) is a known cause of sudden cardiac death. The genetic basis of BrS is not well understood, and no one single gene is linked to even a majority of BrS cases. However, mutations in the gene SCN5A are the most common, although the high amount of phenotypic variability prevents a clear correlation between genotype and phenotype. Research techniques are limited, as most BrS cases still remain without a genetic diagnosis, thus impairing the implementation of experimental models representative of a general pathogenetic mechanism. In the present study, we report the largest family to-date with the segregation of the heterozygous variant NM_198056:c.4894C>T (p.Arg1632Cys) in the SCN5A gene. The genotype-phenotype relationship observed suggests a likely pathogenic effect of this variant. Functional studies to better understand the molecular effects of this variant are warranted.